2016
DOI: 10.1111/tri.12789
|View full text |Cite
|
Sign up to set email alerts
|

Short-term MyD88 inhibition ameliorates cardiac graft rejection and promotes donor-specific hyporesponsiveness of skin grafts in mice

Abstract: SUMMARYRecognition of evolutionarily conserved ligands by Toll-like receptors (TLRs) triggers signaling cascades in innate immune cells to amplify adaptive immune responses. Nearly all TLRs require MyD88 to transduce downstream signaling. MyD88 deficiency has been shown to promote the allograft acceptance in mice. However, direct evidence for therapeutic potential of MyD88 inhibitors remains lacking. Herein, we used a MyD88 inhibitor, namely ST2825, to explore its therapeutic potential and mechanisms in fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Our current findings indicate that TAK-242 monotherapy could disrupt TLR4 signaling to ameliorate intimal hyperplasia at week 2, but the effect was not sufficient to prevent graft atherosclerosis. Previous studies reported that deficient of MyD88 or short-term MyD88 inhibition promoted the survival of grafts 30 , 31 . Downstream of TLR4, two adaptors, MyD88 and TRIF, mediate the signaling.…”
Section: Discussionmentioning
confidence: 95%
“…Our current findings indicate that TAK-242 monotherapy could disrupt TLR4 signaling to ameliorate intimal hyperplasia at week 2, but the effect was not sufficient to prevent graft atherosclerosis. Previous studies reported that deficient of MyD88 or short-term MyD88 inhibition promoted the survival of grafts 30 , 31 . Downstream of TLR4, two adaptors, MyD88 and TRIF, mediate the signaling.…”
Section: Discussionmentioning
confidence: 95%
“…TLRs are well-characterized receptors that recognize conserved components from both own and other organisms and initiate signaling pathways of the innate immune system, thus, enhancing adaptive immune responses. 32 Nearly all TLRs require MyD88 for downstream signal transduction. MyD88 functions as a central mediator of the inflammatory response and can initiate signal transduction from multiple receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-clinical studies using MyD88 or TLR deficient mice have identified both as effective targets to limit IRI, inflammation, and improve transplant outcomes ( 36 ). These early rodent studies utilizing TLR and MyD88 deficient mice have led to the development of numerous biologics targeting TLRs and MyD88, which have shown promise in promoting tolerance or limiting rejection ( 37 42 ). For example, newer agents like Eritoran, which is a synthetic analog of the lipid A portion of lipopolysaccharide (LPS) that can antagonize LPS binding ( 43 , 44 ), or the 2-aminothiazole-derived MyD88 inhibitor TJ-M2010-5, are potent inhibitors of DC activation and promoted long-term heart and skin graft survival in rodents ( 37 ).…”
Section: Directly Targeting Damp Signaling To Improve Outcomesmentioning
confidence: 99%